The God who acts in history : the significance of Sinai - Bartholomew, Craig G., 1961-; Abraham, William J. (William James), 1947- (Grand Rapids, MI. William B Eerdmans Publishing Company, 2020)
Did the decisive event in the history of Israel even happen? The Bible presents a living God who speaks and acts, and whose speaking and acting is fundamental to his revelation of himself. God's action in history may seem obvious to many Christians, but modern philosophy has problematized the idea. Today, many theologians often use the Bible to speak of God while, at best, remaining agnostic about whether he has in fact acted in history. Historical revelation is central to both Jewish and Christian theology. Two major events in the Bible showcase divine agency: the revelation at Sinai in Exodus and the incarnation of Jesus in the gospels. Surprisingly, there is a lack of serious theological reflection on Sinai by both Jewish and Christian scholars, and those who do engage the subject often oscillate about the historicity of what occurred there. Craig Bartholomew explores how the early church understood divine action, looks at the philosophers who derided the idea, and finally shows that the reasons for doubting the historicity of Sinai are not persuasive. The God Who Acts in History provides compelling reasons for affirming that God has acted and continues to act in history. --
Includes bibliographical references (pages 233-248) and indexes
Keywords: Providence and government of God -- History of doctrines; Philosophy and religion; Revelation; Revelation on Sinai